Peran Obligasi Syariah (Sukuk) bagi Pembanguan Nasional - Heri Sudarsono (Jurnal Aplikasi Bisnis, 2017)
Sukuk had contributed to the development and growth of Islamic financial system as it gains an important position in the current financial system. The sukuk issuance lias attract the crowds not only the market players but also the government, the jurist and academicians to explore the viability and competitiveness of current instrument towards the economic development as a whole as well as well being of the human. Despite massive growth of Sukuk issuance, several issues and challenges need to be highlighted in order to ensure smooth growth in the area. Syariah issues, accounting issues and financial issues are considered as critical area that needs more attention. More efforts are needed to make Sukuk as investment of choice. It obtain more collaboration domestically end internationally to achieve that objective. Current situat on displayed the importance ofsukuk in the global market as it becomes National initiative and the competition is not only among the financial institution but it has been competition between countries.